Intercivilizational Cooperation : The Islamic Alternative To The Clash Of Civilizations - Hamidatou ., Mostafa (جامعة الوادي - University of Eloued, 2015)
NTERCIVILIZATIONAL COOPERATION : THE ISLAMIC ALTERNATIVE TO THE CLASH OF CIVILIZATIONS ) , I will address the subject in accordance with the following elements : 1- How real is the Islamic threat ? 2- Islam's position toward the clash of civilizations. • Islam and its civilization in the eyes of western writers • The rise and fall of civilizations • Human beings as the core of civilizations • Characteristics which are vital for civilizational cooperation
مقال
Keywords: Civilizations of Islam ; Clash of civilizations; Rise of civilizations; fall of civilizations; civilizational cooperation